Determinanty prywatyzacji handlu wiejskiego - Ciechomski, Wiesław (Wydział Prawa i Administracji UAM, 1991)
The article is devoted to the conditions of privatization of rural trade. In the first part the Author carries out the analysis of the present demonopolization tendencies and privatization of rural trade. He points to special disproportions of the speed of privatization of rural enterprises run by GS „Samopomoc Chłopska". Then, the Author presents the statistics on the number of new and liquidated rural economic units in trade, services and handicraft in Poland in 1990. The second part of the article presents the obstacles to privatization of rural trade and the possibilities to overcome those obstacles.
Determinants of privatization of rural trade